Pelatihan Tertib Administrasi dan Manajemen Keuangan Pada Kelompok Wanita Tani Sewagati Gamping Yogyakarta - Ika Wulandari; Agus Setiyoko; Rani Dwi Lestari (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
This training aims to increase the understanding of members and management of KWT Sewagati Gamping, Sleman Yogyakarta regarding orderly administration, bookkeeping and simple financial management. Before the community service activities were carried out, KWT Sewagati did not yet have good records of activity administration, finance, bookkeeping and simple financial management. The method of service is training and mentoring. The training activities were held on July 9 2023 by presenting 15 management and members of the KWT Sewagati group. After the training activities, assistance was also provided to KWT Sewagati management in terms of financial and activity records. Evaluation of activities is carried out using pre-test and post-test as well as monitoring activities. After the training and mentoring there was an increase in participants' understanding of the orderly administration of activities to 84%, the level of participants' understanding of orderly financial administration increased to 82%. The increase in participants' understanding of business financial management was 80% and the participants' understanding of simple financial bookkeeping increased to 80%. Overall the activity was successful because it exceeded the target of the Service Team, where the target success rate was at least 70%. Currently KWT Sewagati already has an activity administration and financial administration book, and has implemented it in group activities.